Physiotherapy Management of Musculoskeletal Disorders in Coronavirus Disease: Case Report - Abedi, Mohsen (Journal of Clinical Physiotherapy Research, 2020)
One aspect of Covid 19 is the various musculoskeletal and motor problems that patients face. Due to the novelty of this disease, a study which has examined its various side effects has not yet been published. Therapists have dealt with a number of issues in their clinical experience. Thus, an investigation of musculoskeletal disorders is essential in this disease. In this study, physiotherapy treatments for a case of Covid 19 hospitalization at Masih Daneshvari Hospital were present. A complete evaluation of the patient’s musculoskeletal status was reviewed along with a review of respiratory symptoms, and then a treatment plan. Due to the novelty of this disease, many of its dimensions are unknown. Due to movement disorders in Covid-19 patients, physiotherapy is one of the important components of the treatment program, especially after discharge from the hospital. This small study provides a platform for extensive research on this topic. Keyword: Coronavirus Disease, Covid-19, Musculoskeletal Disorders, Physiotherapy